Residential dual core energy recovery ventilation system for ventilation of northern housing. Issue 5 (September 2019) - Ouazia, B; Won, D.; Arsenault, C; Li, Y
Abstract: Heat/energy recovery ventilation systems are types of HVAC that can reduce energy consumption and improve the ventilation rate of housing in cold climates. Their performance achieved to date has been inadequate due to equipment failures (freezing of cores, noise, etc.). Freezing of cores is common in extremely cold climates. Single core HRV/ERV units are usually equipped with defrost strategies such as recirculation of exhaust stale air across the heat exchanger and back into the supply air to the house. These defrost strategies can undermine ventilation standards (ventilation rate requirement not being met during recirculation). This paper presents a rigorous investigation on the performance of dual core energy recovery system that provided a continuous ventilation rate at outdoor temperatures below -10°C without frost protection. The dual core ERV had higher apparent sensible effectiveness (up to 12% more) and apparent total effectiveness (up to 9% more) than a conventional single core ERV. It showed no sign of frost problems after four weeks of winter testing, continuously provided outdoor air without stopping to defrost, unlike the conventional single core ERV which required up to 7.5 hours defrosting per day, and also provided a higher supply air temperature (up to 3°C) to indoors with a total whole-house energy saving of 4.7%.